(untitled) (Mugda Medical College Journal, 2025)
Acute kidney injury (AKI) is an important public health issue in Bangladesh. There are different reasons behind this. Gentamicin is a commonly used antibiotic prescribed to cure infections and a potential cause of renal tubular damage. An available vegetable Daucus carota Linn. (Carrot) and ACE inhibitor, ramipril, have some nephroprotective properties that alleviates gentamicin induced acute kidney injury. A study was carried out on a group of rats to evaluate the nephroprotective effect of carrot in comparison with ramipril. An experimental study was conducted to demonstrate the effect of ethanolic extract of carrot on blood urea and serum creatinine levels as well as histopathological changes in gentamicin induced nephrotoxic kidneys of a group of rats and the results were compared with a nephroprotective drug ramipril. Blood urea and serum creatinine levels and histopathological changes revealed a significant difference with carrot which is comparable to ramipril in gentamicin induced nephrotoxicity in rats. Carrot has nephroprotective effect that can reduce gentamicin induced nephrotoxicity compared to ramipril. Mugda Med Coll J. 2025; 8(1): 3-7